Trends in gonorrhoea in nine western European countries, 1991–6. Issue 2 (1st April 2000) - Van der Heyden, J H A; Catchpole, M A; Paget, W J; Stroobant, A
Abstract : Objective: To present, describe, and assess trends in gonorrhoea in western Europe between 1991 and 1996. Methods: A European Union concerted action was initiated in 1990 to monitor the prevalence of HIV among patients with a sexually transmitted infection in sentinel networks in western Europe. Data from this concerted action were used to assess trends in gonorrhoea between 1991 and 1996. Where possible, the trends were validated by comparing them with national laboratory reports or data from more extensive sexually transmitted infection surveillance networks. Results: 7192 episodes of gonorrhoea were recorded at 38 sentinel sites in nine countries between 1991 and 1996. In most networks, there was a decline in the number of cases of gonorrhoea among heterosexual men and women. The decline was most marked in the Scandinavian countries. Decreases were also observed among men having sex with men, but in some networks—England and Wales, Netherlands, and Scotland—an increase was observed in more recent years. This increase was mainly the result of an increase in cases among the older age group (25 years and above). The trends observed in six of the sentinel networks were confirmed by trends in national laboratory reports or data from more extensive sexual transmitted infection surveillance systems. Conclusions: These data indicate that, overall, there was a decline in the number of gonorrhoeal cases in western Europe between 1991 and 1996. The results, however, also indicate that in more recent years there was an increase in the number of gonorrhoea cases among men having sex with men in some countries. Further investigations are necessary to determine if this observation is due to an increase in risky sexual behaviours in this population group.